A review of energy internet research considering interactive energy: The blockchain perspective - Wang, Guofeng; Liu, Yuchen; Zhang, Cheng; Zhang, Youbing (Frontiers in Energy Research, 2022)
With the proposal of carbon peak and neutrality goals in China, the new technologies such as multi-energy synergy technology, cyber physical systems and multi-market integration technology have ushered in unprecedented opportunities and challenges. Energy Internet(EI) technology considering interactive energy has come into being. Interactive energy is a mechanism to achieve system balance by integrating economic means and power grid control technology, using "value" as a coordination method. It can promote the development and utilization of distributed renewable energy in the energy Internet, so as to promote the clean, low-carbon and intelligent development of energy. Blockchain can provide effective support for the development and application of the EI because of its decentralized, open, autonomous and information immutable characteristics. In order to better cope with the challenges existing in the EI, this paper designs an analysis framework for the EI from the blockchain perspective, which contains five dimensions, including engineering dimension, technical dimension, economic dimension, environmental dimension and social dimension. And further refines the five dimensions, aiming to comprehensively summarize the research status of the EI, which can promote its application in the development of all industries in society.